PERANAN SUKU BUNGA KREDIT, CAPITAL ADEQUACY RATIO (CAR) DAN LOAN TO DEPOSIT RATIO (LDR) BAGI PERTUMBUHAN EKONOMI INDONESIA - Asril Lisaholet (Economic Research Center, the Indonesian Institute of Sciences (P2E-LIPI), 2022)
Controlling the banking-monetary in such a way needs to be done so that dynamic of real sector growth developed to expected way. This study is intended to analyze the role of credit interest rate instrument, development of capital adequacy ratio (CAR), and loan to deposit ratio (LDR) to Indonesian economics growth in the last ten years. By using multiple linear stepwise regression analyzing method approach, a very significant role simultaneously and partially from credit interest rate instrument and development of CAR push the Indonesian economics growth in a long term were found. Meanwhile, there’s no a significant roles from development of LDR to the Indonesia economics growth in a medium term. The modeling results have adjusted R-square of about 87,80 percent and met all the diagnostic assumption test, while 12,20 percent is explained by other variables outside the model.